UI/UX Design Of A Peer Counseling Website For Universitas Mulawarman Students Using The Design Thinking Method - Suharizman Poerwo, Najwa Caesa Putri Ramadhania; Hario Jati Setyadi; Muhammad Labib Jundillah (Primakara University, 2026)
This study aimed to design a UI/UX-based website for peer counseling services at Universitas Mulawarman to improve accessibility and user experience. The existing counseling service, known as CIRCLE, had limited awareness and relied on non-integrated platforms, which reduced its effectiveness in meeting students’ needs. A user-centered approach was applied using the Design Thinking method, consisting of empathize, define, ideate, prototype, and test stages. Data were collected through surveys and in-depth interviews to identify user problems and expectations. The design process was carried out using Figma, including the development of wireframes, style guides, mockups, and interactive prototypes. Visual enhancements such as 3D icons were also applied to create a more engaging interface. The prototype was evaluated through usability testing using Maze and a System Usability Scale questionnaire. The results showed that the designed interface improved user understanding, navigation, and overall experience. The evaluation produced an average usability score of 77, indicating that the system was acceptable and easy to use. These findings demonstrated that a user-centered UI/UX design could enhance the effectiveness, accessibility, and usability of peer counseling services for university students.